ANALYSIS OF THE UTILIZATION AND MANAGEMENT OF ZAKAT FUNDS BY BAZNAS FOR THE PERIOD 2019-2021 EFFICIENCY STUDY OF ZAKAT METHOD CORE PRINCIPLES - Abdul Wahid; Yayat Sujatna (EKOSSISTEM : Islamic Economics, Banking, Law, System, 2025)
The utilization of zakat funds is the process of using zakat funds to meet the needs of mustahik (zakat recipients) in order to improve social and economic welfare. This research analyzes the efficiency of the utilization and management of zakat funds by the National Zakat Agency (BAZNAS) for the 2019-2021 period using the Zakat Core Principles (ZCP) Method. Using a qualitative approach and secondary data from BAZNAS's financial and performance reports, the study measures effectiveness based on the principles of wealth redistribution, moral values, and social solidarity. The results indicate that BAZNAS has achieved a high level of effectiveness in managing zakat funds. Programs, such as staple food assistance, were implemented quickly and on target, providing a significant positive impact in meeting the consumptive needs of mustahik. BAZNAS is considered successful in optimizing the use of funds through targeted programs and cooperation with local partners, thereby contributing to the improved welfare of zakat recipients. To further increase efficiency, it is recommended that BAZNAS strengthen planning, strategy evaluation, and coordination with local partners to ensure increasingly efficient and well-targeted fund distribution.